Constraining uncertainties in CMIP5 projections of September Arctic sea ice extent with observations - Senftleben, Daniel; Lauer, Axel; Karpechko, Alexey (Journal of Climate, 2020)
In agreement with observations, Earth system models participating in the Coupled Model Intercomparison Project Phase 5 simulate a decline in September Arctic sea ice extent (SIE) over the past decades. However, the spread in their 21st-century SIE projections is large and the timing of the first ice-free Arctic summer ranges between 2020 to beyond 2100. The uncertainties arise from three sources (internal variability, model uncertainty and scenario uncertainty), which are quantified in this study for projections of SIE. The goal is to narrow uncertainties by applying a Multiple Diagnostic Ensemble Regression (MDER). MDER links future projections of sea ice extent to processes relevant to its simulation under present-day conditions using data covering the past 40 years. With this method, we can reduce model uncertainty in projections of SIE for the period 2020-2044 by 30 to 50% (0.8 to 1.3 million km²). Compared to the unweighted multi-model mean, the MDER-weighted mean projects an about 20% smaller SIE and an earlier near-disappearance of Arctic sea ice by more than a decade for a high greenhouse gas scenario. We also show that two different methods estimating internal variability in SIE differ by 1 million km². Regardless, the total uncertainties in the SIE projections remain large (up to 3.5 million km², with irreducible internal variability contributing 30%) so that a precise time estimate of an ice-free Arctic proves impossible. We conclude that unweighted CMIP5 multi-model mean projections of Arctic SIE are too optimistic and mitigation strategies to reduce Arctic warming need to be intensified.